Glycation of soy and pea proteins influences infant gastric digestibility more than intestinal digestibility. (March 2023) - Tang, Jiaying; Wichers, Harry J.; Hettinga, Kasper A.
Abstract: Dry heating of plant proteins occurs during production of plant-based infant formula. To study the effect of dry heating on physicochemical changes and in vitro infant digestion of soy and pea proteins, these proteins were mild dry heated (60 °C) for 6 h and 48 h, in the presence or absence of glucose. In this study, we found that with extended dry heating, the degrees of glycation increased in the presence of glucose. After 48 h of dry heating, the degree of gastric hydrolysis decreased from 2.7% to 0.2% for soy protein and from 2.8% to 0.4% for pea protein, compared to non-treated proteins. Such resistance to gastric digestion was probably due to the extensive protein aggregation induced by glycation. However, the intestinal digestion was less affected, as the degree of hydrolysis was similar at the end of intestinal digestion, ranging from 31.0% to 35.4% for soy protein and 36.7% to 48.5% for pea protein. This may be due to the broad range of proteases in pancreatin negating the effect of glycation. By contrast, for the glucose-free samples, no glycation happened and only limited insoluble aggregates were formed during dry heating. Despite this aggregation, the variation in dry heating duration did not lead to different digestibility. Therefore, 60 °C of mild dry heating will influence the gastric digestion of glucose-containing samples, but will not influence the final intestinal digestibility of all the samples with or without glucose. Graphical abstract: Image 1 Highlights: Glycation occurred only in the protein samples dry-heated with glucose. Glycation-induced aggregation hindered gastric digestion. Diverse enzymes in pancreatin negated the effect of glycation on intestinal digestion. Mild dry heating (60 °C) only led to limited aggregation of glucose-free samples. Digestibility of glucose-free samples was not affected by mild dry heating.